Shariah Marketing Strategy of Micro, Small, and Medium Enterprises Products in Aceh: A Case of Minyeuk Pret - Yusuf, Muhammad Yasir; Jalilah, Jalilah; Kesuma, Teuku Meldi (Jurnal Ilmiah Peuradeun, 2022)
The province of Aceh as an area of Islamic law has a uniqueness where Islamic culture and values cannot be separated. Business activities such as marketing MSME products have great opportunities to be implemented in terms of Sharia values. Minyeuk Pret product is one of Aceh's local perfume brands which has developed quite a bit since 2015. This study aimed to examine the development strategy of Minyeuk Pret products in Aceh with a marketing approach of Sharia values. The research method used was a qualitative descriptive method at all stages of product creation from upstream to downstream. The results show that the product development efforts undertaken by Minyeuk Pret include improving product quality, selling at affordable prices, good service, processes that are tailored to the needs and tastes of the community, as well as providing environmental benefits with sharia marketing. Implementation of Islamic marketing of perfume products consistently will have a characteristic impact on Islamic values in the creation of local MSME perfume products. This study concluded that Minyeuk Pret products must create a positioning value with aspects of the term halal to build Muslim consumer loyalty to fragrance oil products.